Progression of Visual Pathway Degeneration in Primary Open-Angle Glaucoma: A Longitudinal Study - Haykal, Shereif; Jansonius, Nomdo M.; Cornelissen, Frans W. (Frontiers in Human Neuroscience, 2021)
Background: Primary open-angle glaucoma (POAG) patients exhibit widespread white matter (WM) degeneration throughout their visual pathways. Whether this degeneration starts at the pre- or post-geniculate pathways remains unclear. In this longitudinal study, we assess the progression of WM degeneration exhibited by the pre-geniculate optic tracts (OTs) and the post-geniculate optic radiations (ORs) of POAG patients over time, aiming to determine the source and pattern of spread of this degeneration. Methods: Diffusion-weighted MRI scans were acquired for 12 POAG patients and 14 controls at two time-points 5.4 ± 2.1 years apart. Fiber density (FD), an estimate of WM axonal density, was computed for the OTs and ORs of all participants in an unbiased longitudinal population template space. First, FD was compared between POAG patients and the controls at time-point 1 (TP1) and time-point 2 (TP2) independently. Secondly, repeated measures analysis was performed for FD change in POAG patients between the two time-points. Finally, we compared the rate of FD change over time between the two groups. Results: Compared to the controls, POAG patients exhibited significantly lower FD in the left OT at TP1 and in both OTs and the left OR at TP2. POAG patients showed a significant loss of FD between the time-points in the right OT and both ORs, while only the left OR showed a significantly higher rate of FD loss in POAG patients compared to the controls. Conclusions: Our findings suggest that glaucomatous WM degeneration starts at the pre-geniculate pathways and then spreads to the post-geniculate pathways. Furthermore, we find evidence that the trans-synaptic spread of glaucomatous degeneration to the post-geniculate pathways is a prolonged process which continues in the absence of detectable pre-geniculate degenerative progression. This suggests the presence of a time window for salvaging intact post-geniculate pathways, which could prove to be a viable therapeutic target in the future.